A multiregional endogenous growth model with forward looking agents - Johannes Bröcker (European Regional Science Association (ERSA), 2011)
The paper presents a multiregional endogenous growth model designed for calibration with real world data and for numerical policy evaluation. It integrates four strands of research: (1) the Ramsey model of consumer behaviour, (2) Tobin's q-theory of investment, (3) Romer's theory of endogenous growth through horizontal product innovation, and (4) the Dixit-Stiglitz-Ethier theory of intra-industry trade. Integrating the latter into a multiregional model is also an essential ingredient of the New Economic Geography. Thus, the paper is related to this literature as well, but lacks another essential feature of this tradition; the model to be presented does not exhibit catastrophic agglomeration. A symmetric first nature will always generate a "flat earth" steady state equilibrium. The model has an arbitrary (possibly large) number of regions with a representative household and a production sector in each of them. There are three types of goods, non-tradable local goods, horizontally diversified tradables, and designs of tradable products that are the exclusive property of their producers (called "blueprints", for short). Goods are produced combining - in identical proportions for all three of them - four inputs, labour, capital local and tradable goods. Blueprint production benefits from a technological positive externality. Technologies and preferences are uniform across space. Beyond goods markets and real factor markets there is a frictionless global bond market. All markets are perfectly competitive except the tradables market, which is monopolistic in the familiar Dixit-Stiglitz-Ethier style. The engine of sustainable long run growth is the accumulation of blueprints. Agents act under perfect foresight. The paper explains the formal structure, the solution and calibration techniques and illustrates the application by a small example.
Keywords: 330